Optimalisasi Komunikasi Persuasif Koperasi Tani Solok Radjo Katalisator Pertanian Berkelanjutan - Intan, Intan Nabila Khaira; Sarmiati, Sarmiati; Azwar, Azwar (Universitas Muhammdiyah Yogyakarta, 2025)
Solok Radjo Farmers' Cooperative plays a role in promoting sustainable agriculture in Solok Regency. This study analyzes the persuasive communication carried out by the cooperative’s management and the changes in farmers' thinking and behavior as a result of this communication. Using a constructivist paradigm with a case study approach, data was collected through observation, interviews, and documentation. The Elaboration Likelihood Theory is applied to understand how persuasion is received and influences farmers' attitude changes. The findings show that persuasive communication is conducted through group discussions, field visits, collaborations, and quarterly meetings. This strategy effectively enhances farmers' understanding, particularly through field visits that encourage them to continue farming. One of the most influential persuasive methods is providing information about the promising coffee market opportunities, which motivates farmers to adopt sustainable agricultural practices. Additionally, education and mentoring from the cooperative’s management have encouraged some farmers to switch to organic fertilizers after understanding their benefits. However, these changes have not yet been consistently implemented and have not created a significant impact across the entire farming community. Therefore, more intensive and continuous communication efforts are needed.